2021
DOI: 10.1182/blood.2021011871
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycosylation of anti-SARS-CoV-2 spike IgG is a prothrombotic stimulus for platelets

Abstract: A subset of patients with COVID-19 become critically ill, suffering from severe respiratory problems and also increased rates of thrombosis. The causes of thrombosis in severely ill COVID-19 patients are still emerging, but the coincidence of critical illness with the timing of the onset of adaptive immunity could implicate an excessive immune response. We hypothesised that platelets might be susceptible to activation by anti-SARS-CoV-2 antibodies and contribute to thrombosis. We found that immune complexes co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 42 publications
3
70
0
Order By: Relevance
“…5 F, G), these findings further confirm that immunothrombosis contributes to the platelet dysfunction in COVID-19 [10] , [28] . In line with the work of Bye et al, SARS-CoV-2 IgG can cause platelet hyperactivity [59] , what supports our findings that recombinant COVID-19 plasma reduces positive impact of LMWH therapy ( Fig. 3 A–E).…”
Section: Discussionsupporting
confidence: 93%
“…5 F, G), these findings further confirm that immunothrombosis contributes to the platelet dysfunction in COVID-19 [10] , [28] . In line with the work of Bye et al, SARS-CoV-2 IgG can cause platelet hyperactivity [59] , what supports our findings that recombinant COVID-19 plasma reduces positive impact of LMWH therapy ( Fig. 3 A–E).…”
Section: Discussionsupporting
confidence: 93%
“…In the studies of Larsen et al, Hoepel et al, Bye et al and Pongracz et al, a common, liquid chromatography – mass spectrometry (LC–MS)-based method was employed to characterize total, anti-S, and to a limited extent anti-SARS-CoV-2 nucleocapsid (N) IgG glycosylation following their affinity purification [ 15 , 26 , 27 , 31 ]. This approach builds on microtitration plate-based adsorption of antibodies to viral proteins using a modification of enzyme-linked immunosorbent assay (ELISA) antibody detection methods.…”
Section: Methods For the Assessment Of Antibody Glycosylation In Covid-19mentioning
confidence: 99%
“…Bye et al reported on the association of anti-S IgG1 afucosylation with prothrombotic platelet activation using in vitro models and highlighted the role of a platelet-specific Fc receptor FcγRIIa [ 27 ]. This finding is remarkable, as the FcγRIIa is not known to prefer afucosylated IgGs [ 2 ], and molecular insights as to how afucosylation contributes to prothrombotic platelet activation are lacking.…”
Section: Functional Consequences Of Altered Fc Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, elevated frequencies of CD16a+ monocytes were another antecedent in patients with more severe outcomes [43]. Immune complexes contained recombinant SARS-CoV-2 spike protein and aberrantly glycosylated anti-spike IgG with enhanced platelet-mediated thrombosis on von Willebrand Factor in vitro [69]; • Autoantibodies: SARS-CoV-2 infection can trigger autoimmune diseases such as myocarditis, and many single cases have been reported in the literature. In this review, we focus on large case series that help assess the prevalence of autoantibodies.…”
Section: Proinflammatory or Immunosuppressive Factorsmentioning
confidence: 99%